A Systematic Review and Economic Evaluation of Sumatriptan Nasal Spray Versus its Oral Tablet - Golnoosh Alipour Haris; Nayyereh Ayati; Ali Mehramizi; Peivand Ghasemzadeh; Mahshid Arabi; Shekoufeh Nikfar (Tehran University of Medical Sciences, 2021)
Background: Sumatriptan is one of the leading medicines in migraine treatment. This study aimed to evaluate the cost-effectiveness (in the context of Iran) of sumatriptan nasal spray versus its oral tablet for treating migraine headaches. Methods: A systematic review of the literature was performed to evaluate the clinical effectiveness of sumatriptan nasal spray compared to its oral tablet. The search was conducted in five major scientific databases from 1990 to December 2018. The effectiveness outcomes were 2-h pain relief and 24-h recurrence rate, which then were translated into Quality-Adjusted Life-year (Qaly). Local costs data were identified based on official tariffs in Iran's public and private sectors, with ratios of %80 and %20, respectively. Costs were converted from Iranian Rial rates (IRR) to US Dollars (USD), using the currency exchange rate of 42000 IRR/USD. A 1-year decision tree was adopted for the economic evaluation, conducted from a payer perspective in the Iranian healthcare setting. The final results were presented by Incremental Cost-Effectiveness Ratio (ICER), which showed the extra cost for one additional QALY gained. ICER was compared to Iran's national willingness to pay (WTP) threshold, which is 2709 USD. The robustness of the results was analyzed using Deterministic Sensitivity Analysis (DSA). Results: The results showed that sumatriptan nasal spray (20 mg, for $0.714 per puff) compared to sumatriptan oral tablet (50 mg, with a weighted mean price of $0.238) had an incremental QALY of 0.028 and incremental cost of $0.21 per attack, per person-year. ICER was calculated to be 2617 USD/QALY, which is below Iran's national WTP threshold. DSA results showed that the model is mainly sensitive to the price of sumatriptan nasal spray. Conclusion: Sumatriptan nasal spray was a more cost-effective medicine than sumatriptan oral tablet in Iranian patients with migraine.